PENINGKATAN KETERAMPILAN BIDAN DALAM PELAYANAN KOMUNITAS DENGAN TERAPI PRENATAL MASSAGE WITH LOVE DI WILAYAH PESISIR KOTA BENGKULU - Dewiani, Kurnia (Universitas Bengkulu, 2023)
In general, discomfort during pregnancy is back pain, cramps, and leg swelling. The unpleasantness is also prone to occur in pregnant women who are in coastal areas. The low economic situation makes pregnant wives work to help support the family income. The use of drugs is not suggested to overcome maternal complaints. The research results show how to overcome the problem by doing a prenatal massage with love. The aim is to apply prenatal massage with love to increase the quality of pregnancy care services in the community, especially in the coastal area of Bengkulu City. Training midwives implemented the method in the designated target area. This research-based service involves lecturers, students, and midwives in the coastal area of Bengkulu City, both those stored in the Puskesmas and the Independent Midwife Practice (PMB) owner. The results of the activity objectives and plans have been achieved and run smoothly. The conclusion is that the community's skills and quality of service are following the target, namely 80%, reducing discomfort in the form of back pain, leg swelling, and leg cramps in pregnant women 75% on visits to midwives. Improvement of at least 25% of midwives' ability to conduct entrepreneurship to develop community practice.